Devenir styliste. Des trajectoires genrées dans les écoles de mode - Nicolas Divert (Éducation et Socialisation)
Since the 1960’s, the dressing field, commonly referred to as fashion, mainly focuses on activities with high added value. Among these activities, clothes designing symbolises its dynamism and the designer is its key figure. Often personified by men in a field of activities which is identified as feminine, a traditional sexual division of labour gets to be seen. Based upon an ethnographical study conducted in two high-end fashion school located in Paris, this piece proposes to study the way boys and girls’ trajectories are being constructed and differentiate from one another along the course of their studies. As they are quite few to be trained, boys are sought after and the « scar » linked to their unorthodox path turns into a source of distinction. The study shows however that these masculine trajectories raise questions related to their sexuality so much so that sex, gender and sexuality must be grasped altogether.